Analisis Perbandingan Keputusan Masyarakat Menggunakan Bank Konvensional dengan Bank Syariah - Rohmat, Siti; Arsyad, Dea; Tiar Harahap, Hasan (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2025)
Individual decisions in choosing a financial institution are a crucial aspect influenced by the environment and quality of service. This study stems from the phenomenon of low public understanding of Islamic banking in Sukamerang Village, the dominance of conventional banks, and limited access to Islamic banking services. Observations show that most people, including members of the Majlis Taklim study group, are not clearly aware of, or even completely unaware of, Islamic banking services. Based on these findings, this study aims to identify the banking products used by the community and compare the community's decisions in choosing between conventional and Islamic banks in Kersamanah Subdistrict, Garut Regency. These findings are expected to contribute to improving Islamic financial literacy and more inclusive policy-making. The method used in this study is a qualitative approach, specifically a descriptive research type. The primary data sources were obtained from interviews and observations with the village head and residents of Sukamerang Village, involving 30 informants. Based on the research findings, it can be concluded that the residents of Sukamerang Village utilize both conventional and Islamic banking services, with a stronger preference for conventional banks. This is due to factors such as ease of access, proximity, and long-standing usage habits. However, Islamic banks are beginning to be chosen for certain aspects, such as opening accounts for children, ease of applying for business capital, and work-related reasons. The most commonly used services include savings, KUR products, and transaction services such as transfers, cash deposits and withdrawals, e-commerce top-ups, and electricity token purchases. Preference for conventional banks is also evident in terms of the number and frequency of transactions, as well as the use of digital payment methods such as SMS and mobile banking. These findings highlight the need to improve literacy and access to Islamic banking services to make them a more competitive alternative among the public.